Implementasi Kebijakan Portal Satu Data Sekadau pada Dinas Komunikasi dan Informatika Kabupaten Sekadau - Agus Rayadin; Ida Rochmawati; Pardi Pardi (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This research examined the process of implementing the Sekadau One Data Portal policy by the Department of Communication and Informatics of Sekadau Regency, and determined the factors that influence it. This research was inspired by the fact that the One Data Indonesia policy has not been implemented optimally at the regional level, especially in the management of accurate, integrated, and accountable sectoral data. The research was descriptive qualitative, and it used four variables of policy implementation according to the theory of Edward III: communication, resources, disposition, and bureaucratic structure. The results indicated that the policy implementation continues to encounter a number of challenges, including: small number and quality of human resources, low budget allocation, poor coordination between divisions in the Office of Communication and Informatics, as well as insufficient outreach and training on data management.In addition, the Office of Communication and Informatics as the custodian of the data is not yet backed by a sufficient bureaucratic system and standard operating procedures. The implications of these findings are significant in enhancing institutional capacity, offering qualified human resources, and instituting technical regulations to facilitate more efficient and sustainable data governance. This research is expected to advance the practice of open data policy and data-based governance in the regional level.